The Learning Effect of Blended Learning Based on Google Class Room and Initial Mathematics on Mathematic Representation and Resilience of Students in the Covid-19 Pandemic - Ayuni Khairiyyah; Mulyono; KMS. Muhammad Amin Fauzi (Britain International for Academic Research (BIAR) Publisher, 2021)
The success of students in taking mathematics lessons also greatly affects the factor of their initial mathematical abilities. Students' initial mathematical abilities are prerequisite abilities that students have before participating in the learning material that will be given. Therefore, students' initial knowledge is indeed an important part of students so that they have good abilities in solving a mathematical problem. (Depdiknas, 2005) states that students' initial knowledge is important for teachers to know before starting with their learning. In addition, students' initial mathematical abilities are also useful as a foothold in the beginning of each student's mathematics so that the teacher will find it easier determine a method or strategy that is suitable for use in the classroom so that the learning that is carried out will be more effective and efficient, (Fatimah, 2016: 13). The results of a preliminary study conducted on class VII teachers of SMPIT Ulil Albab Pematangsiantar shows that teachers have not identified students' initial mathematical abilities as a supporting factor for the success of learning mathematics. The same thing was expressed by (Suprapta, Suharta, & Irawan, 2016: 69) yang stated that most teachers tend to directly explain the subject matter to be discussed without wanting to know the ability of students' prior knowledge. Even though good learning provides opportunities for students to connect initial knowledge with new knowledge on the material being studied, train students' skills and abilities in the classroom.